Exploring barriers, needs, and facilitators for clinical and translational research in Oklahoma: A sequential mixed-methods study - Motolani E. Ogunsanya; Laura A. Beebe; Janis E. Campbell; Nicole Holmes; Timothy VanWagoner; Judith James (Journal of Clinical and Translational Science)
Abstract